Treatment of Light-Induced Degradation for Solar Cells in a p-PERC Solar Module via Induction Heating - Min-gwang Seok; Junhee Kim; Yonghwan Lee; Yoonkap Kim; Yangdo Kim; Soo Min Kim (Energies, 2021)
In the photovoltaic industry, there is great interest in increasing the power output of solar cells to achieve grid parity and to promote the widespread use of solar cells. However, despite many developments, a phenomenon called light-induced degradation causes the efficiency of solar cells to deteriorate over time. This study proposes a treatment that can be applied to cells within solar modules. It uses a half-bridge resonance circuit to induce a magnetic field and selectively heat Al electrodes in the solar cells. The electrical state of a solar module was measured in real time as it was being heated, and the results were combined with a kinetics simulation using a cyclic reaction. As the temperature of the solar module increased, the time taken to reach the saturation point and the recovery time decreased. Moreover, the value of the saturation point increased. The light-induced degradation activation energy was similar to results in the existing literature, suggesting that the kinetic model was valid and applicable even when 72 cells were connected in series. This demonstrates that an entire solar module can be treated when the cells are connected in series, and in future multiple modules, could be connected in series during treatment.